Analisis Dan Perancangan Ulang Leaf Trolys Yang Memenuhi Kaidah-Kaidah Ergonomi (Studi Kasus di PTP. Nusantara VI Pabrik Teh Danau Kembar) - Emelia Sari (JURNAL TEKNIK INDUSTRI, 2011)
Leaf trolys have been utilized in PTPN VI to transfer tea-leaves between workstations. 75% of operators suffer from manual handling injuries after using  leaf trolys mostly on their back and waist. Rapid Upper Limb Assessment (RULA) method is  utilized to analize whether those injuries caused by working posture. The analysis states all working postures not ideal and need to be changed immediately (level 4). Ideal working postures achieved by redesigning of leaf trolys i.e. new handle, hidraulics, changing the wheel size and  positition. Compliance of ergonomy principles is evaluated by RULA. The analysis reports all working postures have degraded from level 4 to level 1 or 2. Time evaluation reports mostly working postures have reduced the standard time,  especially in tea-leaves transfer activity from leaf trolys to DIBN 1 machine inlet by 62,39%.